Molecular dynamics simulations of the solidification of pure aluminium - Papanikolaou, Michail; Salonitis, Konstantinos; Jolly, Mark R. (Springer, 2020)
Despite the continuous and remarkable development of experimental techniques for the investigation of microstructures and the growth of nuclei during the solidification of metals, there are still unknown territories around the topic of nucleation during solidification. Such nanoscale phenomena can be effectively observed by means of Molecular Dynamics (MD) simulations which can provide a deep insight into the formation of nuclei and the induced crystal structures. In this study, MD simulations have been performed to investigate the solidification of Aluminium melt and the effects of process parameters such as the cooling rate and hydrostatic pressure on the final properties of the solidified material. A large number of Aluminium atoms have been used in order to investigate the grain growth over time solidification. The population of the Face Centred Cubic (FCC) and amorphous (or non-crystalline) phases has been recorded during the evolution of the process to illustrate the nanoscale mechanisms during solidification. Finally, the exothermic nature of the solidification process has been effectively captured by measuring the temperature of the Al atoms during grain formation.
Keywords: Molecular dynamics; Solidification; Nucleation; Pressure; Aluminium